Pengaruh Mindfulness Body Scan Terhadap Penurunan Tingkat Stres Pada Siswi SMA Di Pondok Pesantren Hidayatullah Tanjung Uncang - Mira Agusthia; Yulianti Wulandari; Eva Arinda (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stress is something that often occurs in schools and Islamic boarding schools or boarding schools. Where this stress occurs because there are more learning demands than those who attend public schools. Besides this stress can be treated with pharmacology and also non-pharmacological techniques, namely with a mindfulness body scan. Purpose: to find out whether there is an effect of mindfulness body scans on reducing stress levels in high school students. Methods: Quasi-experimental quantitative research one group pre test-post test design with a sampling technique using purposive sampling with a sample of 20 people. Results: the research obtained before being given therapy was in the moderate stress level category of 14 people (70.0%). And after being given therapy, the result was that the stress level after being given a mindfulness body scan was in the low stress level category for 11 people (55.0%). the results of the analysis test showed that there was an effect of mindfulness body scans on reducing student stress levels with a p-value of 0.000 (p0.05). Conclusion: There is an effect before and after mindfulness body scans on reducing stress levels in high school children.